2018
DOI: 10.1016/j.imr.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-arthritic activity of Cinnamomum cassia bark extract in experimental models

Abstract: BackgroundCinnamomum cassia iswidely used as a traditional medicinal plant for the treatment of rheumatoid arthritis.ObjectiveThe present study aimed to assess the anti-arthritic activity of C. cassia bark hydroalcoholic extract (CCHE) in different arthritic animal models.MethodsIn formaldehyde model, sub-plantar administration of 0.1 ml of formaldehyde (2% v/v) into the right hind paws of Wistar albino rats on days 0 and 3. The rats were divided into six groups as follows: normal control, disease control, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 46 publications
4
16
0
Order By: Relevance
“…Later, cinnamomulactone (0.1, 1, 10 and 100 μM), a new phytocompound from the EETC, was reported to be inhibitory to the expression of MMP-1, MMP-3 and IL-1β in rheumatoid arthritis synovial fibroblasts [49]. Moreover, in 2018, Sharma et al reported that WEBC (50, 100 and 200 mg/kg) can significantly reduce IL-1, MDA, TNF-α levels and joint swelling in a concentration-dependent manner in rats with CFA-induced and formaldehyde- induced arthritis [72].…”
Section: Pharmacologymentioning
confidence: 99%
“…Later, cinnamomulactone (0.1, 1, 10 and 100 μM), a new phytocompound from the EETC, was reported to be inhibitory to the expression of MMP-1, MMP-3 and IL-1β in rheumatoid arthritis synovial fibroblasts [49]. Moreover, in 2018, Sharma et al reported that WEBC (50, 100 and 200 mg/kg) can significantly reduce IL-1, MDA, TNF-α levels and joint swelling in a concentration-dependent manner in rats with CFA-induced and formaldehyde- induced arthritis [72].…”
Section: Pharmacologymentioning
confidence: 99%
“…Extract [83], chromone extract [84], chromones: divaricatol, ledebouriellol and hamaudol [85], polysaccharide [86] (i) Anti-inflammatory [83,84,86], (ii) Analgesic [85,87], (iii) Immunomodulatory [87] Gui zhi, Rou gui Cinnamomum cassia Presl Extracts [88][89][90], cinnamic acid [90], cinnamomulactone [91] (i) Anti-inflammatory [90], (ii) Anti-arthritic, reduces joint swelling [88], (iii) Inhibitory activity against matrix metalloproteinases [91], (iv) Improved clinical symptoms and inflammatory markers [89] Ma huang Ephedra sinica Stapf, other Ephedra spp. Polysaccharides [92,93] (i) Anti-inflammatory, immunosuppressive [92,93] Bai zhu Atractylodes macrocephala Koidz Extract [94], atractylone [95], atractylenolide I [94], atractylenolide III [96], Sesquiterpenoids [97]; three new compounds [98] (i) Anti-inflammatory [94][95][96][97][98] Chuan xiong, xiong qiong…”
Section: Syndromes In 2018 Guidelinementioning
confidence: 99%
“… 28 Energy consumption stimulation by TNF-α occurs via the action of TNF-α on protein and lipid metabolisms with the resultant reduction in energy intake by provoking anorexia, thus leading to cachexia. 29 , 30 Prazosin revealed a promising inhibitory impact on the expression of inflammatory cytokine TNF-α.…”
Section: Discussionmentioning
confidence: 99%